Adolescents with Mild Stunting Show Alterations in Glucose and Insulin Metabolism - Carla Danusa da Luz Santos; Ana Paula Grotti Clemente; Vinicius José Baccin Martins; Maria Paula Albuquerque; Ana Lydia Sawaya (Journal of Nutrition and Metabolism, 2010)
Purpose. To evaluate glucose and insulin profiles in adolescents with mild stunting and overweight in order to assess the possibility of increased predisposition to diabetes. Subjects and Methods. The study population consisted of 66 pubertal adolescents classified as mildly stunted (height-for-age z scores ≥−2 and <−1) or of normal stature, as well as overweight (body mass index ≥85th percentile) or normal weight. Beta-cell function and insulin resistance were evaluated according to the homeostasis model assessment (HOMA). Results. In the group with mild stunting, glucose, insulin, and HOMA-IR levels were significantly higher in overweight adolescents compared with those of normal weight, whereas HOMA-B levels were significantly lower. Adolescents with mild stunting showed significantly higher accumulations of body and abdominal fat than their normal stature counterparts. Conclusions. The presence of mild stunting was associated with higher levels of glucose and insulin, diminished function of beta cells, and increased insulin resistance. These results reinforce the need for intervention in adolescents with mild stunting.